2009
DOI: 10.1080/02705060.2009.9664321
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Use and Diet of the Round Goby (Neogobius melanostomus) in Coastal Areas of Lake Michigan and Lake Huron

Abstract: The non-indigenous round goby (Neogobius melanostomus) has caused considerable impact in the Laurentian Great Lakes. We sampled round gobies in shoreline habitats and tributary systems of Lake Michigan and Lake Huron to determine patterns of habitat use and diet, including the extent dreissenid mussels were consumed. Along the shoreline, round goby catch did not significantly differ based on the presence of emergent vegetation, but deeper habitats were preferred relative to shallow areas closer to shore. In tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 42 publications
6
31
1
Order By: Relevance
“…Our results in conjunction with evidence on round goby diets (Cooper et al 2009;Ruetz et al 2009) suggest that round goby predation effects on Dreissena density are not uniform across coastal areas of eastern Lake Michigan. In our enclosure experiment, the presence of large round gobies (i.e., 5, 10, and 15 individuals/m 2 ) significantly decreased Dreissena abundance in Muskegon Lake.…”
Section: Discussionsupporting
confidence: 45%
See 4 more Smart Citations
“…Our results in conjunction with evidence on round goby diets (Cooper et al 2009;Ruetz et al 2009) suggest that round goby predation effects on Dreissena density are not uniform across coastal areas of eastern Lake Michigan. In our enclosure experiment, the presence of large round gobies (i.e., 5, 10, and 15 individuals/m 2 ) significantly decreased Dreissena abundance in Muskegon Lake.…”
Section: Discussionsupporting
confidence: 45%
“…We used round goby densities of 5-15 individuals/m 2 in enclosures, which are not uncommon in the Great Lakes (Ray and Corkum 2001;Barton et al 2005;Johnson et al 2005) with densities as high as 133 individuals/m 2 reported in areas of Lake Michigan (Chotkowski and Marsden 1999). However, the size and density of round gobies in cages were likely greater than round gobies inhabiting littoral habitats in Muskegon Lake given the size and number of round gobies collected in fyke nets (Cooper et al 2007(Cooper et al , 2009Ruetz et al 2007). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations